Reactions of Some Schiff base Complexes of Cu(II) and Ni(II) with Sulfur-Donor Anions - T. Esmadi, Fatima; Irshiadat, T. (Asian Journal of Chemistry, 2010)
Schiff base complexes of Ni(II) and Cu(II) containing sulfur donor anions have been synthesized and characterized. These Schiff bases are derived from reaction of 8-aminoquinoline and salicylaldehyde (HL1 ), 8-aminoquinoline and 2-hydroxynaphthaldehyde (HL2) and 2-arninobenzoic acid and 2-hydroxynaphthaldehyde (HL3). Some of the obtained comp!exes contain only the Schiff base bonded to the metal, others have sulfur-donor anion in addition to the Schiff base such as thiocyanate, pyrrilodinedithiocarbamate (Pyr) and piperazinedi-(dithiocarbamate) (Pip). Structures have been suggested on the basis of elemental analysis, conductivity, spectral and magnetic measurements. No general formula was found for the obtained complexes. Copper in most of its complexes is suggested to be tetra-coordinate mononuclear, one complex is suggested to be dinuclear and one as tetranudear. However,. nickel is suggested to be tetra- or hexacoordinate and one complex is formulated as dinuclear.